Bio-ecology and integrated management of the red palm weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae), in the region of Valencia (Spain) - Dembilio, Óscar; Jaques, Josep A. (Benaki Phytopathological Institute, 2020)
The invasive red palm weevil, Rhynchophorus ferrugineus Olivier (Coleoptera: Curculionidae), is one of the most destructive pests of palms in the world. It is widely distributed in all continents and has been reported on 26 palm species belonging to 16 different genera. In the Mediterranean basin, R. ferrugineus has become the major pest of palms, mainly Phoenix canariensis hort. ex Chabaud, an endemic palm to the Canary Islands widely used as ornamental. In this manuscript we summarize the research that the UJI-IVIA Unit has carried out on this pest. The first objective of our work was to determine different bio-ecological parameters of R. ferrugineus under natural conditions in a Mediterranean climate. Washingtonia filifera is the only palm species included in our studies showing mechanisms of complete resistance against R. ferrugineus. Although Chamaerops humilis and Phoenix theophrasti show antixenotic and antibiotic mechanisms of resistance, respectively, they cannot be considered as resistant against R. ferrugineus. Under Mediterranean climate, the preimaginal development of R. ferrugineus in P. canariensis takes 666.5 DD and the weevil can complete 13 larval instars. Based on the results obtained, less than one generation per year can be expected in areas with a mean annual temperature (MAT) below 15ºC and more than two in those with MAT above 19ºC. Oviposition in R. ferrugineus is also strongly affected by temperature. The thresholds for oviposition and egg hatching obtained are very close to MAT registered in most of the northern shore of the Mediterranean basin. Under these circumstances, no new infestations would be expected during most of the winter. The second objective has been to improve chemical and biological control. Both imidacloprid and Steinernema carpocapsae in a chitosan formulation are highly effective against R. ferrugineus in the field. Different timings and product combinations were studied, and high efficacies were obtained in all cases. An indigenous strain of Beauveria bassiana, found naturally infecting pupae of R. ferrugineus, resulted highly virulent against all developmental stages of the weevil in the laboratory. Additionally, adults of either sex inoculated with the fungus efficiently transmitted the disease to healthy adults of the opposite sex and this result confirmed the potential of B. bassiana as a biological control agent against this pest. These results should help developing an integrated management program against this pest.